Design and Validation of a Radio‐Frequency Identification‐Based Device for Routinely Assessing Gait Speed in a Geriatrics Clinic. Issue 5 (23rd February 2018) - Barry, Lisa C.; Hatchman, Laura; Fan, Zhaoyan; Guralnik, Jack M.; Gao, Robert X.; Kuchel, George A.
Abstract : Objectives: To evaluate the feasibility, acceptability, and validity of a radio‐frequency identification (RFID)‐based system to measure gait speed in a clinical setting as a first step to using unobtrusive gait speed assessment in routine clinical care. Design: Feasibility study comparing gait speed assessed using an RFID‐based system with gait speed assessed using handheld stopwatch, the criterion standard. Setting: Outpatient geriatrics clinic at a Connecticut‐based academic medical center. Participants: Clinic attendees who could walk independently with or without an assistive device (N=50) and healthcare providers (N=9). Measurements: Gait speed was measured in twice using 2 methods each time before participants entered an examination room. Participants walked at their usual pace while gait speed was recorded simultaneously using the RFID‐based system and a handheld stopwatch operated by a trained study investigator. After 2 trials, participants completed a brief survey regarding their experience. At the end of the study period, clinic healthcare providers completed a separate survey. Results: Test‐retest reliability of the RFID‐based system was high (intraclass correlation coefficient = 0.953). The mean difference ± standard deviation in gait speed between the RFID‐based system and the stopwatch was –0.003±0.035 m/s (p=.53) and did not differ significantly according to age, sex, or use of an assistive walking aid. Acceptability of the device was high, and 8 of 9 providers indicated that measuring gait speed using the RFID‐based system should be a part of routine clinical care. Conclusion: RFID technology may offer a practical means of overcoming barriers to routine measurement of gait speed in real‐world outpatient clinical settings.